Towards Washable Wearable Antennas: A Comparison of Coating Materials for Screen-Printed Textile-Based UHF RFID Tags - Tiiti Kellomäki; Johanna Virkki; Sari Merilampi; Leena Ukkonen (International Journal of Antennas and Propagation)
(Radio frequency identification) RFID tags integrated into clothing enable monitoring of people without their conscious effort. This requires tags to be an unnoticeable part of clothing and comfortable to wear. In this study, RFID antennas were screen printed on two different fabrics, six different coating materials for the (integrated circuits) ICs were applied, and the reliability of these RFID tags was tested with moisture and laundry tests. Generally, glue-type coating materials were easier to handle and could be spread precisely. All the tags were operational immediately after the coatings were applied, and five of the coating materials were seen to protect the IC from detaching in the laundry. It was found that the uneven fabric surface caused discontinuities and breaks in narrow conductors, and thus hard coatings may also be needed to keep the tag from breaking in laundry.